2005
DOI: 10.2527/2005.831160x
|View full text |Cite
|
Sign up to set email alerts
|

Corn hybrid affects in vitro and in vivo measures of nutrient digestibility in dogs

Abstract: Corn is a commonly used ingredient in dry pet foods because there is a stable supply and it is a relatively inexpensive source of nutrients. Corn hybrids are available that are higher in CP and amylose and lower in phytate concentration than conventional hybrids. Approximately 500 mg of high-protein (HP), high-protein, low-phytate (HPLP), and high-amylose (HA) corn were compared with conventional (CONV) corn and amylomaize starch (AM) in triplicate and exposed to pepsin/hydrochloric acid and pancreatin to simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
(40 reference statements)
3
21
0
Order By: Relevance
“…Minor differences in maize composition were also found in previous studies comparing GM and non-GM maize (2,51). Although nutrient differences between the Bt maize and isogenic maize may be a result of the cry1Ab gene insertion, natural variation in nutrient composition is frequently observed between non-GM maize varieties (12,16,17,21,24,36,58). Furthermore, it has been concluded in a study by Barros et al (3) that environmental factors can affect maize composition more than the genetic modification itself.…”
Section: Discussionmentioning
confidence: 51%
“…Minor differences in maize composition were also found in previous studies comparing GM and non-GM maize (2,51). Although nutrient differences between the Bt maize and isogenic maize may be a result of the cry1Ab gene insertion, natural variation in nutrient composition is frequently observed between non-GM maize varieties (12,16,17,21,24,36,58). Furthermore, it has been concluded in a study by Barros et al (3) that environmental factors can affect maize composition more than the genetic modification itself.…”
Section: Discussionmentioning
confidence: 51%
“…Bednar et al (2000) used various ingredients that contained protein including wheat, corn, wheat gluten meal, beef and bone meal, poultry byproduct meal, or poultry meal. Diets used by Clapper et al (2001) contained chicken bone residue next to a protein source and Gajda et al (2005) used various protein sources. Although 5 other studies were found to report apparent ileal CP and AA digestibility values in adult dogs, their data were not used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A previously reported data set (Hendriks et al, 2012) was supplemented with data from 5 studies (Zentek, 1995;Johnson et al, 1998;Gajda et al, 2005;Hendriks et al, 2013;Tjernsbekk et al, 2014) to contain data on 158 canine diets used in fundamental nutritional research, formulated to evaluate specific ingredients or investigate specific technological treatments. The data set contained information on BW, food intake, dietary N content, and apparent fecal and apparent ileal digestibility of N. From 24 diets reported in 6 studies (Bednar et al, 2000;Clapper et al, 2001;Gajda et al, 2005;Tjernsbekk et al, 2014), apparent ileal digestibility values of individual AA were also collected.…”
Section: Data Used To Derive Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Well-digested products cause stiff and shaped stools. The fecal consistency may vary on a scale of 1 to 5 from watery to solid (5,(17)(18)(19)(20) or some studies rate watery as 1 whereas others rate it as 5 (14,21).…”
Section: Introductionmentioning
confidence: 99%